2021
DOI: 10.1186/s12917-020-02700-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and characterisation of Domestic Cat Hepadnavirus (DCH) from blood and liver tissues of cats in Malaysia

Abstract: Background A new domestic cat hepadnavirus (DCH, family Hepadnaviridae) was first reported from whole blood samples of domestic cats in Australia in 2018, and from cat serum samples in Italy in 2019. The pathogenesis of DCH is unknown, but it was reported in cats with viraemia (6.5–10.8%), chronic hepatitis (43%) and hepatocellular carcinoma (28%). Recent reports suggest that DCH resembles the human hepatitis B virus (HBV) and its related hepatopathies. This study aims to detect and characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
82
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(103 citation statements)
references
References 27 publications
14
82
3
Order By: Relevance
“…DCH has a genome of approximately 3.2 kb of DNA, which similar to other hepadnaviruses, has four overlapping open reading frames (ORFs) encoding for the polymerase (L), surface (S), core (C) and X proteins. Genome sequences derived from DCH-positive domestic cats in Australia [ 18 ], Italy [ 20 ], and Malaysia [ 21 ], show 97.0–98.3% nucleotide similarity to each other. Recently a putative DCH recombinant strain was found in Thailand, suggesting a possible role of recombination in DCH evolution [ 22 ].…”
Section: Domestic Cat Hepadnavirus (Dch)mentioning
confidence: 99%
See 4 more Smart Citations
“…DCH has a genome of approximately 3.2 kb of DNA, which similar to other hepadnaviruses, has four overlapping open reading frames (ORFs) encoding for the polymerase (L), surface (S), core (C) and X proteins. Genome sequences derived from DCH-positive domestic cats in Australia [ 18 ], Italy [ 20 ], and Malaysia [ 21 ], show 97.0–98.3% nucleotide similarity to each other. Recently a putative DCH recombinant strain was found in Thailand, suggesting a possible role of recombination in DCH evolution [ 22 ].…”
Section: Domestic Cat Hepadnavirus (Dch)mentioning
confidence: 99%
“…Subsequent screenings with molecular assays (degenerate PCR and real time PCR), carried out by independent research groups around the world, have revealed positivity rates of 6.5% (six in 54) in Australia [ 18 ], 10.8% (42 in 390) in Italy [ 20 ], 12.4% (26 in 209) in Thailand [ 22 ], and 12.3% (31 in 253) in Malaya [ 21 ] in whole blood and serum samples. Moreover, DCH DNA has been detected in liver tissue [ 21 , 23 ], with a higher positivity rate (14%; 13 in 84) than in blood/serum [ 21 ]. The formation and maturation of DCH particles in the nucleus and/or cytoplasm of infected hepatocytes suggests that hepatocytes are the initial localization of the virus as described in HBV infection [ 22 ].…”
Section: Domestic Cat Hepadnavirus (Dch)mentioning
confidence: 99%
See 3 more Smart Citations